Le conjoint de fait a-t-il vocation au bénéfice de l’assurance-vie prévue par l’avenant F.A.Q. n° 34 ? À propos d’une décision récente de la Cour supérieure - Lluelles, Didier (Assurances, 1984)
What is the exact meaning of "conjoint" (normally translated in English as "wife" or "spouse") referred to in the endorsement respecting insurance of persons of the automobile insurance policy? Does it mean the insured's wife who has left him, or the woman with whom he has lived for several years? At first glance, it would seem that it is the legal wife who should be considered as the "conjoint" for the purposes of the automobile insurance policy, but judge Turmel is inclined to think that it is the victim's companion, on condition that she has lived with him for at least three years. Mr. Lluelles' article is interesting because he deals with both possibilities as they apply to the payment of benefits. It appears that, while the Civil Code considers the legal wife to be the "conjoint", it is the companion (for at least three years) who is recognized by the Quebec Automobile Insurance Law, at least in the present case.